High frequency CuBr vapor brightness amplifier; Electron Devices and Materials (EDM), Annual Siberian Russian Workshop; Micro/Nanotechnologies and Electron Devices - Musorov I. S. Ilia Sergeevich; Torgaev S. N. Stanislav Nikolaevich; Evtushenko G. S. Gennady Sergeevich; Kulagin A. E. Anton Evgenievich; Evtushenko T. G. Tatjyana Gennadjevna (2017, 2017)
Title screen